CDCA7 enhances STAT3 transcriptional activity to regulate aerobic glycolysis and promote pancreatic cancer progression and gemcitabine resistance - Dijie Zheng; Yazhu Deng; Lu Deng; Zhiwei He; Xinghao Sun; Yanyu Gong; Binbin Shi; Deqin Lu; Chao Yu (Cell Death and Disease)
Abstract Cell division cycle associated 7 (CDCA7) plays a role in various malignancies, especially pancreatic cancer (PC). However, its expression pattern and functional significance in PC require further research. Therefore, this study aimed to investigate CDCA7 expression levels and biological functions in PC using in vitro and in vivo experiments. Western blotting, immunohistochemistry, and real-time polymerase chain reaction were performed to detect CDCA7 expression in PC cells and tissues. Additionally, the biological functions of CDCA7 were assessed using cell proliferation, wound healing, and Transwell assays. CDCA7 overexpression promoted PC cell proliferation, migration, and invasion, and increased resistance to the chemotherapy drug gemcitabine, possibly through enhanced aerobic glycolysis. Additionally, immunoprecipitation assay showed that CDCA7 interacted with STAT3 protein and affected the transcriptional regulation of hexokinase 2. Conclusively, targeting CDCA7 might be a promising therapeutic strategy to increase gemcitabine sensitivity by inhibiting glycolysis in PC cells.